A prospective, cross sectional open label clinicoepidemiological study of vitamin B-12 deficiency in adolescent children - Singh, Chaturbhuj; Garg, Pukhraj; Sodawat, Rishi (International Journal of Contemporary Pediatrics, 2018)
Background: Megaloblastic anemia is becoming most common forms of anemia in adolescents during recent years. In India limited studies are available on megaloblastic anemia. The main aim of the study was to determine the incidence, prevalence, and various morphological patters and complications of vitamin B12 deficiency anemia in adolescents. Methods: Hospital based cross sectional observational study of 100 adolescents anaemic patients (excluding anemia of bone marrow failure, haemolytic anemia associated with jaundice and organomegaly, aplastic anemia, leukaemia and anemia associated with chronic inflammatory disease) admitted in paediatric ward from 2016 to2017 was done. In every case detailed history, examination along with blood investigation done including complete blood count, blood indices and peripheral blood smear for morphology. In every case serum B12 level was estimated. Results: Out of 100 cases 38% were deficient with female dominance. Significant association (p<0.05) was found between B12 deficiency and vegetarian diet, macrocytic peripheral film, pancytopenia, knuckle pigmentation and neurological symptoms. Conclusions: Deficiency of B12 deficiency is common among the adolescents, which is common in vegetarian’s diet patterns. Supplementation through implemented nutritional programmes and education regarding diet patterns may overcome this deficiency.